Rancang Bangun Aksaranesia.Co Berbasis Waterfall Model Sebagai Media Gerakan Literasi Sekolah SMPN 4 Kota Yogyakarta - Cahyo Febri Wijaksono; Syunu Trihantoyo (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Literacy is important to master in the 21st century. However, in reality, students' low literacy skills are exacerbated by the use of conventional media and the implementation of the School Literacy Movement (GLS) which is not yet optimal. This research aims to (1) analyze the validity of Aksaranesia.co as GLS media at SMPN 4 Yogyakarta City; (2) analyzing the compatibility of Aksaranesia.co as GLS media at SMPN 4 Yogyakarta City; and (3) analyzing the usability of Aksaranesia.co as GLS media at SMPN 4 Yogyakarta City. This research is Research and Development (R&D), with a waterfall model consisting of 5 stages, namely requirements and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance. The results of this R&D are: (1) Aksaranesia.co obtained a mean score of 3.30 on content validity, and 3.66 on construct validity, so it is very valid; (2) Compatibility testing on Android 10.0-13.0, as well as Google Developer tools shows that Aksaranesia.co is 100% compatible; and (3) Aksaranesia.co through usability testing with a percentage of 96.68% or very feasible. Aksaranesia.co is expected to provide implications in efforts to develop literacy media to support the 2030 SDGs.